Implementation of Web-Based Interactive Students’ Worksheets with a Scientific Approach for Algebraic Forms Concepts - Nurhayati, Sovi Endah; Lestari, Puji (Jurnal Pendidikan MIPA, 2022)
The purpose of this study was to describe the achievement of student learning outcomes using web-based interactive Student Worksheets through a scientific approach to the concept of algebraic forms and to determine student responses in the use of web-based interactive Student Worksheets. The method used in this study is a type of qualitative descriptive research. The results showed that the achievement of student learning outcomes using interactive web-based Student Worksheets with a scientific approach to the concept of algebraic forms achieved the Minimum Completeness Criteria. Student responses to the use of web-based interactive Student Worksheets showed a good response. The use of interactive web based Student Worksheets can be very effective in improving student learning outcomes if the lesson plans, work steps and giving the types of questions on the Student Worksheets are made appropriately and systematically. Keywords: students’ worksheets, scientific approach, algebra. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp765-779